Factores incidentes en la disminución de la recaudación tributaria en la municipalidad provincial de Sánchez Carrión año 2017 - Ruiz Reyes, Flor María (2019)
The main objective of this research is to determine what are the factors that influence the decrease in tax collection in the Provincial Municipality of Sánchez Carrión, year 2017. Whose research problem was What are the factors that influence the decrease in tax collection tax collection in the Provincial Municipality of Sánchez Carrión, year 2017? The research design is descriptive. The population was made up of 13,618 active taxpayers, the respective sample being 1021. The survey and documentary analysis were used in the data collection, the respective instruments being the questionnaire and analysis tables. The main results are that the factors that affect the decrease in tax collection are legal, political, administrative, economic, financial, and institutional management. Likewise, it has been obtained that in 2017 compared to 2016 there was a reduction of 8.19% in municipal tax collection.